An Exploratory Study on the Influence of Cognitive and Affective Characteristics in Programming-Based Making Activities - Pappas, I.; Papavlasopoulou, S.; Giannakos, M.; Sampson, Demetrios (2017)
© 2017 IEEE. Programming-based making activities are at the core of teaching strategies to engage young students in learning programming for developing computational thinking skills. Despite the initial evidences of enthusiastic participation in such activities, more systematic studies are needed to better understand drivers of students' intentions to participate in programming-based making activities. In this paper, we present an exploratory study which aim to address this issue by examining the interrelations among cognitive (i.e., perceived usefulness, perceived ease of use) and affective (i.e., enjoyment) characteristics for both boys and girls. To this end, we build on complexity theory and configuration theory, present a conceptual model, and employ fuzzy-set Qualitative Comparative Analysis (fsQCA) on a sample of 105 young students, to identify such interrelations. The findings provide insights on how the examined factors may have a different influence for boys and girls, an outcome that can be used to re-design educational programs targeting maximizing engagement regardless gender.